Between‐case standardized mean difference effect sizes for single‐case designs: a primer and tutorial using the scdhlm web application. Issue 1 (19th December 2016) - Valentine, Jeffrey C.; Tanner‐Smith, Emily E.; Pustejovsky, James E.; Lau, T. S.
Executive summary: Single‐case research designs are critically important for understanding the effectiveness of interventions that target individuals with low incidence disabilities (e.g., physical disabilities, autism spectrum disorders). These designs comprise an important part of the evidence base in fields such as special education and school psychology, and can provide credible and persuasive evidence for guiding practice and policy decisions. In this paper we discuss the development and use of between‐case standardized mean difference effect sizes for two popular single‐case research designs (the treatment reversal design and the multiple baseline design), and discuss how they might be used in meta‐analyses either with other single‐case research designs or in conjunction with between‐group research designs. Effect size computation is carried out using a user‐friendly web application, scdhlm, powered by the free statistical program R; no knowledge of R programming is needed to use this web application.